The Effect of STEM (Science, Technology, Engineering, and Mathematics) Based Learning Approach on Critical Thinking Skills and Cognitive Learning Outcomes of Class X SMA Negeri 1 - Ipah Budi Minarti; M. Anas Dzakiy; Dila Nilautama (At-Tasyrih: jurnal pendidikan dan hukum Islam, 2022)
21st century learning refers to students for 4C (Critical Thinking, Communication, Collaboration, and Creativity) namely skills that students must have, such as problem solving skills, critical thinking skills, teamwork skills and communication skills. Critical thinking skills are something that must be instilled in students so that students are able to explore a problem and can solve it effectively and efficiently. Efforts that can be made to improve the quality of learning involve students to be able to build their knowledge and be able to solve a problem. One way to overcome this is by using the STEM (Science, Technology, Engineering, and Mathematics) approach. This study aims to determine the effect of the STEM approach in learning to improve critical thinking skills and cognitive learning outcomes of class X SMA Negeri 1 Tahunan. The subjects in this study were students of class X MIPA. The sampling technique used in this research is cluster random sampling. This research method is True Experimental Design research using the Pretest and Posttest Control Group method. There are two classes in this study, namely the experimental class and the control class. Analysis of the t test data is used to see the difference in the mean between the two samples. The t-test of the cognitive learning outcomes of students in the experimental class and control class in the pretest obtained ttable <tcount, namely 1.66 <6.11. The t-test of the cognitive learning outcomes of students in the experimental class and control class in the Posttest obtained ttable 1.66 <tcount 6.145. The results of research between critical thinking and student learning outcomes there are significant differences, so this study can be concluded that the STEM approach is effective for improving critical thinking and student learning outcomes.